Enhanced Learning Outcomes with Audio in E-learning: An Analysis - Rautela, Vijayshree (International Journal of Advanced Corporate Learning (iJAC), 2024)
Audio in any form whether as narration, sound effects, background music, or commentary can make e-learning more interesting for a learner. It completes the sensory engagement in a learner where the visual meets the auditory to comprehend a learning component. As an instructional designer and trainer, over the years, I have created several e-learning courses for adult learners with and without audio. The learning outcomes of the two when compared using several surveys and other evaluation mechanisms showed that learners not only prefer learning instruction that has audio but were also able to retain the learning and apply it to their jobs. This paper analyses how the level of learning outcomes is better in e-learning courses with audio than without audio. It shares some of the science and research that supports this. In addition, it describes the learner surveys and evaluation mechanisms that I have used to prove this and discusses the national and international compliances that make audio a mandate in e-learning to support of my analysis.